Ets21c Governs Tissue Renewal, Stress Tolerance, and Aging in the Drosophila Intestine. - Mundorf, J.; Donohoe, C.D.; McClure, C.D.; Southall, T.D.; Uhlirova, M. (Cell reports, 2019)
Homeostatic renewal and stress-related tissue regeneration rely on stem cell activity, which drives the replacement of damaged cells to maintain tissue integrity and function. The Jun N-terminal kinase (JNK) signaling pathway has been established as a critical regulator of tissue homeostasis both in intestinal stem cells (ISCs) and mature enterocytes (ECs), while its chronic activation has been linked to tissue degeneration and aging. Here, we show that JNK signaling requires the stress-inducible transcription factor Ets21c to promote tissue renewal in Drosophila. We demonstrate that Ets21c controls ISC proliferation as well as EC apoptosis through distinct sets of target genes that orchestrate cellular behaviors via intrinsic and non-autonomous signaling mechanisms. While its loss appears dispensable for development and prevents epithelial aging, ISCs and ECs demand Ets21c function to mount cellular responses to oxidative stress. Ets21c thus emerges as a vital regulator of proliferative homeostasis in the midgut and a determinant of the adult healthspan.